Development of Biosciences in the Integrated Qur'an Textbooks of Lampung Local Wisdom Values - Hakim, Nasrul; Hayati, Dwi Kurnia; Susbiyanto, Susbiyanto (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The process of learning science in the qur'an should be integrated with its own national culture, known as local wisdom. The obvious issue is the absence of references that can be used in learning. And therefore, the current research was carried out to develop biosciences in the integrated qur'an textbooks with lampung's local sacred values. Conducted through 4D development model that includes defining, designing, developing, and disseminating, The validation results of the designing expert obtained a score of 89% considered excellent. The results of the material expert validation obtained a score of 92% considered excellent. Furthermore, the validation of the linguist obtained a score of 90% considered very good. the results on responses of Tadris Biology lecturers obtained a score of 85% considered very good. The results of the limited trial among Biology students was of 87.25% considered very good. Based on the findings, it can be concluded that the teaching book products developed are definitely useful for the learning process.Keywords: textbooks, biosciences, Qur'an, local wisdom